The scale of homogeneity in the Las Campanas redshift survey - Amendola, Luca; Palladino, Emilia (Arxiv, 1999)
We analyse the Las Campanas Redshift Survey using the integrated conditional density (or density of neighbors) in volume-limited subsamples up to unprecedented scales (200 Mpc/
Gesehen am 20.11.2017